QUANTITATIVE AND QUALITATIVE EVALUATION OF MORPHOMETRIC INDICES IN SHIRAK REGION FROM THE VIEWPOINT OF EVALUATION OF ECOLOGICAL SITUATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
The morphometric characteristics of relief are the most important factors influencing on the ecological conditions of the area. They influence on many natural and social processes and phenomena having some ecomorphological characteristics. Relief morphometric indices evaluation and mapping was realized in Shirak region for discovering the above-mentioned features.
Keywords: Shirak Region; morphometric characteristics